Relation between the Introduction of Remote Teaching as a Result of the COVID-19 Pandemic and the Quality of the Academic Teaching of Accounting - Anna FUKS (Communications of International Proceedings, 2020)
The aim of this paper is to present the relation between the COVID-19 pandemic and the obligatory introduction of remote teaching and the quality of the academic teaching of Accounting. The aim was achieved through research. The selected research method was a survey questionnaire sent in an electronic form. The survey should be treated as a pilot study. It was carried out in 7 groups of first-year students pursuing a first cycle programme at a public institution of higher education in the field of Finance and Accounting (full-time and extramural modes) and Management (full-time mode), who attended classes in Financial Accounting run exclusively by the author of this survey during the summer term 2019/2020. The most important and crucial results of the survey permitted the formulation of new research hypotheses, which will be verified at successive stages of the research: (1) combination of elements of remote and traditional teaching (blended teaching) might lead to the best performance in teaching Accounting; (2) effective remote teaching cannot take place without building, sustaining, and improving proper interpersonal teacher–student relationships and, to an extent, relationships between students.
Keywords: teaching methods; remote teaching; blended learning; teaching Accounting